Karakteristik Mi Basah Tapioka dengan Penambahan Kacang Pagar (Phaseolus lunatus) - Nahdatul Ikhlas; Shanti Fitriani; Rahmayuni Rahmayuni (Jurnal Teknologi dan Industri Pertanian Indonesia, 2020)
Lima beans (Phaseolus lunatus) have been valued to increase proteins and improve the quality of wet noodles.  The purpose of this research was to get the best formulation of tapioca and lima beans paste on the quality and sensory character of wet noodles based on Indonesian National Standard.  This research was conducted experimentally by using a completely randomized design with four treatments and four replications.  The treatment in this research was the ratio of tapioca and lima beans paste such as 90:10, 80:20, 70:30 and 60:40.  Data obtained were statistically analyzed using analysis of variance and continued with duncan’s new multiple range test (DNMRT) at a 5% level.  The result of this research showed that the ratio of tapioca and lima beans paste significantly affected moisture, ash, protein, fat, starch, carbohydrate contents as well as elongation and sensory characteristic of color, flavor, elasticity, stickiness and taste.  The best treatment in this research was the ratio of tapioca and lima beans paste (70:30) where moisture content of 61.25%, ash content of 0.87%, protein content of 4.32%, fat content of 0.86%, starch content of 30.29%, carbohydrate content of 32.67% and elongation of 32.50%.  The descriptive test showed that wet noodles had yellow color, flavouring lima beans, chewy, a little sticky and lima beans taste and overall assessment hedonically was favoured by panelists. Keywords: wet noodles, tapioca and lima beans paste